Chaos in a System with an Absolute Nonlinearity and Chaos Synchronization - Victor Kamdoum Tamba; Karthikeyan Rajagopal; Viet-Thanh Pham; Duy Vo Hoang (Advances in Mathematical Physics)
A system with an absolute nonlinearity is studied in this work. It is noted that the system is chaotic and has an adjustable amplitude variable, which is suitable for practical uses. Circuit design of such a system has been realized without any multiplier and experimental measurements have been reported. In addition, an adaptive control has been applied to get the synchronization of the system.